PENGARUH PENERAPAN E-FILLING, TINGKAT PEMAHAMAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN FORMAL WAJIB PAJAK ORANG PRIBADI - Ninis Nur Solichah; Isnalita -; Noorlailie Soewarno (Universitas Airlangga, 2019)
The purpose of this research to determine the effect of e-Filing implementation, level of tax comprehension, and tax sanction in carrying out their tax obligations. The data were obtained from 178 questionnaires distributed to individual taxpayers who use e-Filing. The population in this research are taxpayers who have used the online SPT reporting program, e Filing. The sample in this research are 178 individual taxpayers. The method of this sampling is using convenience sampling method. The data analysis technique used is multiple linear regression. The result of this research shows that e-Filing implementation, tax sanction and the level of comprehension taxation has significant effect on compliance. The contribution of this research can provide information about the ease of reporting tax returns through e-filing so that more people report taxreturns and pay their taxes and expected to increase knowledge in the field of taxation.